Tinjauan Estetika Hiasan Kaca Patri Pada Gereja Katolik Inkulturatif Paroki Santo Fransiskus Asisi Berastagi Berdasarkan Prinsip Seni Rupa - Siregar, Samuel Joan Parasian (Mahesa Research Center, 2021)
This study aims to describe the aesthetic quality of the stained glass decoration work at the Catholic Church of St. Francis of Asisi Berastagi based on the principles of fine arts, especially in the aspects of unity, balance, rhythm, proportion, composition, and center of interest. This study used descriptive qualitative method. The subjects in this study were part of the stained glass in the Catholic Church of St. Francis of Asisi, which is also a sample in this study, amounting to five samples. The sampling technique used was total sampling. The results of this study explain that the visual quality of the stained glass works in the Catholic Church of St. Francis, if viewed based on the principles of art, shows some deficiencies in these works can be seen from the number of works that only get points below three (<3), wrong the only thing is that there are still most of the works that have shortcomings in terms of composition and there is no balance in them, this is due to the color selection and placement of objects that are not quite right, plus there are still some deficiencies in the objects that are formed that are not proportional. However, even so, there are still some works that have sufficient to excellent quality, where these works are able to get points above three (> 3).